(untitled) (Estudios humanísticos. Geografía, historia y arte, 1992)
For the city of León, the absolutist restoration of 1814 meant the beginning of the repression for a reduced group of liberals, a task in which the bishop of the diocese figured prominently. This article is dedicated to describing the process followed by one of them: the retired colonel D. Luis de Sosa.